Filtering Power Divider With Ultrawide Stopband and Wideband Low Radiation Loss Using Substrate Integrated Defected Ground Structure - Han, Changxuan; Tang, Deshan; Deng, Zhixian; Qian, Huizhen Jenny; Luo, Xun (IEEE microwave and wireless components letters, 2021)
In this letter, a novel substrate integrated defected ground structure (SIDGS) resonant cell is proposed. Such SIDGS resonant cells can not only introduce an ultrawide stopband for spurious suppression but also achieve low radiation loss in a wideband, which can be easily implemented in passive circuits with high performance. To verify this mechanism, a filtering power divider (FPD) using the folded stepped-impedance scheme is developed. Here, two coupled SIDGS resonant cells are cascaded at the arms of the power divider to achieve a filtering response with ultrawideband harmonic suppression. The fabricated FPD is operated at 2.87 GHz (i.e., the passband center frequency f_{0} ) with a 3-dB fractional bandwidth (FBW) of 23%, which exhibits the 28-dB attenuation upper stopband with a low radiation loss even up to 25 GHz (i.e., 8.71 f_{0} ).